Pulping Of Vetiver Grass With NH4OH-KOH-AQ Mixtures - Panitnad Chandranupap; Pravitra Chandranupap (ASEAN Journal of Chemical Engineering, 2011)
The detail analysis of the heat and mass transfer between the droplet containingsuspended solids and the drying gas was carried out numerically. The temperature andmoisture distributions within the slurry droplet were calculated during the first andsecond drying phases. The parametric study revealed that the droplet drying timedecreases with increasing the drying gas temperature and decreasing the dropletdiameter.